Političko-pravni sistem zaštite ljudskih prava i sloboda u Bosni i Hercegovini / Political-Legal System of Protection of Human Rights and Freedoms in Bosnia and Herzegovina - Šmitran, Mirjana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
Respect and protection of human rights and freedoms are important factors of development and progress in every democratic society. Political-legal system of protection of human rights and freedoms in Bosnia and Herzegovina is fully based on international human rights law. The most prominent are the European Convention for the Protection of Human Rights and Fundamental Freedoms and fifteen international documents on human rights and freedoms contained in Annex I of the Dayton Peace Agreement. Direct application of these documents is prescribed by the Constitution of Bosnia and Herzegovina.